Analisis Pemanfaatan Media Sosial Instagram sebagai Media Pembelajaran Jarak Jauh pada Mata Kuliah Pendidikan Kewarganegaraan - Khusnul Khotimah; Mukhamad Murdiono; Mariyani Mariyani (Departement of Mathematics Education, 2023)
This study aims to describe the use of Instagram social media as a learning medium in civic education courses and to describe the factors that support and hinder the use of Instagram social media as learning media in citizenship education courses. Data collection techniques using observation, documentation and interviews. Selection of informants based on purposive, namely the selection based on the purpose of this study. The research was carried out in a class of students of the Management Department of Sriwijaya University on the subject of democracy. The results of the research that have been carried out show that lectures through Instagram are very interesting and fun, students become more active because students feel more free to express their opinions so that almost all of them share their opinions in lectures. Distance learning using the internet network and several tools that must be owned by every educator and student there are supporting and inhibiting factors in the lecture process. Supporting factors include: a) The learning process becomes more relaxed. b) The available features vary, c) The learning materials are interesting, d) Easy to reach. In addition to the supporting factors, there are also inhibiting factors in the use of Instagram social media as a learning medium. The inhibiting factors for the use of social media as a distance learning medium are: a) unstable network, b) inadequate gadgets and c) explanations of material that are difficult to understand and d) some students do not use Instagram usernames using real names so it is difficult to recognize student name.